Effects of ash-forming temperature on recycling property of bottom ashes from rice residues. (15th December 2015) - Zhang, Yi; He, Fang; Gao, Zhenqiang; You, Yanyan; Sun, Peng
Highlights: Ash water solubilities decrease by 80% when temperature increases from 400 to 800 °C. K, Na, S, and Cl are major dissolved elements in bottom ashes of rice residues. Recycling property of ash from different parts of the same crop vary considerably. Abstract: In this paper, effects of ash-forming temperature on recycling property of bottom ashes obtained from combustion of rice straw and rice husk were investigated. Ash solubility and element solubility were chosen for representing recycling property and they were determined based on the measurement of element content using X-ray Fluorescence Spectrometer (XRF). Results show that water solubilities of both bottom ashes decrease with increasing ash-forming temperature and the water solubility of rice straw ash is higher than that of rice husk ash. Investigations also reveal that the easily soluble elements are K, Cl, S, Na in rice straw ash and K, S in rice husk ash. While the solubilities of K and Na decrease with the increasing ash-forming temperature, the solubilities of S and Cl are independent upon this temperature. Difference between the two ashes indicates that the recycling property of ashes from different parts of the same crop varies considerably.